PENGUATAN NILAI-NILAI PANCASILA DAN PENANAMAN WAWASAN KEBANGSAAN PADA GENERASI MUDA - Risma Yuliana Saputri; Fatma Ulfatun Najicha (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2023)
Globalization is a very common phenomenon. With globalization, the exchange of information flows from various countries occurs so quickly, people really benefit from this. However, the growing epidemic will also have a negative impact on Indonesia, namely the waning sense of nationalism and patriotism among the people, especially the younger generation. With existing technological advances, various digital platforms such as social media can be misused by the younger generation, which of course has a negative effect on their behavior. Thus, indirectly globalization can result in the erosion of Pancasila values in the younger generation because of deviant behavior, in the form of crime, immorality, and various other negative behaviors. In this case, the values of Pancasila need to be re-instilled so that Pancasila can be maintained as the identity of the nation. This study aims to provide information about the form of Pancasila implementation and the importance of strengthening Pancasila values in social life in order to improve the personality of the younger generation in Indonesia in the era of globalization. This research method uses literature study by reading and seeking information from books, journals, and other literature study sources that are relevant to the subject matter to be discussed.